The Party Politics of the EU and Immigration - Odmalm, Pontus; SpringerLink (Online service) (London : Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2014)
This book explores the changing nature of party competition in four West European countries. It pays special attention to how different ideological positions give rise to contradictory cues when parties engage with atypical election issues like the EU and immigration.
Keywords: Science